Plankton composition, abundance and diversity in hilsa (Tenualosa ilisha) migratory rivers of Bangladesh during spawning season - Ahsan, Dewan Ali; Kabir, AKM Nazrul; Rahman, Md Mofizur; Mahabub, Shahad; Yesmin, Rumana; Faruque, Md Hasan; Naser, Md Niamul (Dhaka University Journal of Biological Sciences, 2012)
Hilsa (Tenualosa ilisha) is one of the flagship diadromous fish species of Bangladesh that migrate only through the Ganges?Meghna river system route. The biological profile of plankton from the Padma, Meghna and Tetulia reference river sites during 2011 spawning season of hilsa showed that in total of 58 taxa of plankton were present. Of which, 19 taxa (32.76%) were of phytoplankton and 39 taxa (67.24%) of zooplankton. Phytoplankton group belonged to Cyanophyceae (6 taxa), Chlorophyceae (7 taxa) and Bacillariophyceae (6 taxa) while zooplankton including Protozoa (10 taxa), Rotifera (19 taxa), Copepoda (4 taxa), Cladocera (5 taxa) and Ostracoda (1 taxon). The average abundance of plankton was recorded as 194.05 ± 82.58 indiv/l. The highest abundance of total plankton (692 indiv/l) was observed in Godagari, Rajshahi (Station 3) and was lowest (4.00 indiv/l) in Charghat, Rajshahi (Station 2). The highest abundance (49 indiv/l) of total zooplankton was observed in Godagari and lowest (1 indiv/l) in Charghat with mean value of 19.46 ± 4.12 indiv/l. The highest species richness (SR = 45) was observed in Daulotkhan, Vhola (Station 9) and the lowest (SR = 3) in Charghat (Station 2), with mean value of 17.10±4.408. Shannon?Weiner species diversity index (H?) ranged from 3.334 in Daulotkhan (Station 9) to 1.5 in Charghat, (Station 2) with mean value of 2.717 ± 0.147. Based on the plankton profile it may be concluded that the biological quality of hilsa migratory river was not alike throughout the route which may restrict the migration up to up steam and spontaneous spawning of hilsa. DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11516 Dhaka Univ. J. Biol. Sci. 21(2): 177-189, 2012 (July)